Propagação e genotoxicidade de Alternanthera brasiliana (L.) Kuntze (Amaranthaceae) - Rocha, Bruna Nery (2013)
Alternanthera brasiliana (L.) Kuntze (Amaranthaceae) is a species known as penicilina, terramicina, doril or carrapichinho. Studies have proved that the extract of the leaves has analgesic, anti-inflammatory and healing. Based on the medicinal use of this species work aimed to propagate vegetatively in vitro and ex vitro A. brasiliana, and to evaluate the genotoxic, anti-proliferative and anti-mutagenic aqueous extract of the leaves of plants from four cropping systems through the Allium cepa test as well as the quantification of the content of polyphenols, flavonoids and chlorogenic acid. Propagation by cuttings of new shoots ex vitro were used, apical, medium and basal cuttings treated medium MS (0 and 20%) with addition of AIB to the liquid medium (0.0 and 2.5 mg L-1). For micropropagation were used apical and nodal segments were inoculated on MS medium with combinations of NAA (0.0 and 0.05 mg L-1) and BAP (0.0 and 0.5 mg L-1). Evaluations of potential genotoxic, anti-proliferative and anti-mutagenic, roots of Allium cepa bulbs were immersed for 24 hours in aqueous extracts by infusion of the dried leaves of A. brasiliana four sources: Campus UFSM; micropropagation, cuttings and greenhouse, all with concentrations of 5 and 20 g L-1. The same extracts were used for the quantification of secondary metabolites, flavonoids and polyphenols, through spectrophotometer and chlorogenic acid by high performance liquid chromatography. Apical cuttings, median and basal can be used for propagation presenting rooting and survival above 62%. In general, plants from middle and basal cuttings show better results than the apical, suggesting that these would be the most suitable for the production of seedlings. In vitro micropropagation apices showed significantly higher results for nodal segments and the use of growth regulators naphthaleneacetic acid (NAA) (0.05 mg L-1) and benzylaminopurine (BAP) (0.5 mg L-1) was not significant. Plants regenerated in vitro acclimatized showed no significant difference between treatments, with the highest survival percentage (72.57%) occurred in plants from the apical medium supplemented with 0.05 mg L-1 NAA and 0, 5 mg L-1 BAP. In Allium cepa was observed that the mitotic index is superior in cell subjected to leaf extracts from the field (5 g L-1) and leaf extract of cuttings (20 g L-1) did not differ from the negative control in distilled water. The other treatments showed potential anti-proliferative with reduced mitotic index did not differ from the positive control in glyphosate 5%. Only the extract of the leaves of the greenhouse (20 g L-1) cells to genotoxic effects of A. cepa, where the number of cells with chromosomal abnormalities did not differ from the positive control. Occurred anti-mutagenic activity of the leaf extract of Campus UFSM (20 g L-1), on the cells of A. cepa, undergoing changes in glyphosate 5%, recovering from the mutagenic effect. Regarding the quantification of metabolites produced higher concentration of polyphenols and flavonoids chlorogenic acid in the samples collected from the field.